Impact of Enterococcus italicus ONU547 on the growth and acclimatization of micropropagated Rubus fruticosus L. and Paulownia tomentosa Steud. plants to ex vitro conditions - Nadiia Tytarenko; Nataliia Tesliuk; Andrii Merlich; Thomas Haertle; Volodymyr Ivanytsia (BioTechnologia, 2023)
Clonal micropropagation is an effective method for plant reproduction, applicable in both scientific and industrial domains. However, a significant number of microclones are lost during the ex vitro acclimatization process. To address this, the introduction of beneficial microorganisms into the rhizosphere of micropropagated plants could have a positive effect on the survival rates and external characteristics of acclimatized plantlets. The aim of this study was to determine the protective and growth-promoting potential of Enterococcus italicus ONU547 and its effect on micropropagated plants during acclimatization. The antagonistic activity of the bacteria was determined using the agar block method. Lepidium sativum L. seeds were inoculated with bacterial suspensions at concentrations of 10 6 , 10 7 , and 10 8 CFU/ml. Subsequently, the roots of the microclones were treated with suspensions of 10 6 and 10 7 CFU/ml, and biometric characteristics were measured. The results demonstrated antagonistic properties against various phytopathogenic fungi, including Aspergillus niger, Cladosporium cladosporioides, Alternaria alternata, Alternaria tenuissima, Rhizoctonia cerealis, Penicillium expansum, and Paecilomyces variotii. Inoculation of L. sativum L. seeds resulted in improved germination rates, increased root numbers, and enhanced root and shoot lengths. Similarly, the effects of the studied bacteria on Rubus fruticosus L. and Paulownia tomentosa Steud. during the acclimatization stage led to higher survival rates, increased shoot lengths, greater node numbers, and larger leaf areas. A concentration of 10 7 CFU/ml was identified as optimal for inoculating the microclones. The findings indicate that E. italicus ONU547 holds promise for the inoculation of micropropagated plants during the acclimatization process. Further research is recommended to establish the specific interaction mechanisms between these bacteria and plants.